MOF (Metal Organic Framework) modified rice husk biochar composite material as well as preparation method and application thereof
Through the preparation of MOF modified rice husk biochar composite, the problem of low adsorption performance of existing adsorbents is solved, efficient adsorption and good chemical stability are achieved, and it has wide application prospects in rare earth ion recovery.
Patent Information
- Application Number
- CN202411919947.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In the prior art, the adsorbents used for rare earth ion recovery have low adsorption performance, which limits their wide application in rare earth ion recovery, especially the poor adsorption effect on La(III).
The MOF modified rice husk biochar composite material is used to combine rice husk biochar with Fe-MOF to form a composite material with a high specific surface area and active sites, achieving specific adsorption of La3+.
Highly efficient adsorption of La3+ is achieved, with a maximum adsorption amount of 288.89 mg g-1, and the composite material has good chemical stability and recyclability, and is suitable for treating wastewater or waste gas containing La3+.
Smart Images

Figure CN119633776A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the technical field of rare earth ion recovery, and specifically to a MOF-modified rice husk biochar composite material and a preparation method and application thereof. Background Art
[0002] Rare earth ions are strategically important to countries seeking to develop high-precision industries due to their excellent physical and chemical properties, and are therefore called "industrial vitamins". The rare earth mining process produces a large amount of low-concentration wastewater containing rare earth elements (with a concentration range of 0.8-130 mg L -1 ), thus forming rare earth waste. In view of the scarcity and non-renewable nature of rare earth resources, as well as the potential non-biodegradability and toxicity of rare earth ions, the recycling of rare earth ions has important economic and environmental significance.
[0003] To date, a variety of methods have been developed in the field of rare earth recovery, including chemical precipitation, extraction, ion exchange and adsorption. Among these recovery methods, adsorption has attracted much attention due to its advantages such as environmental protection, low cost, strong selectivity and effectiveness at low concentrations. At present, although a variety of adsorbents have been developed for recovering rare earth ions from aqueous solutions, such as clay minerals, imidazolate zeolite frameworks, cellulose nanocomposites, and graphene oxide-based nanocomposites, the low adsorption properties of these traditional materials limit their widespread application in rare earth ion recovery.
[0004] As one of the most abundant and useful lanthanide elements, lanthanum is widely used in the production of precision optical glass and ceramics, agriculture, steel processing and catalysis. However, due to the genotoxicity of La(III) to human peripheral blood lymphocytes, La-containing wastewater discharged from industrial processes will pollute the environment and endanger human health. Therefore, it is urgent to develop an adsorbent that can efficiently adsorb La(III). Summary of the invention
[0005] To this end, an embodiment of the present invention provides a MOF-modified rice husk biochar composite material and a preparation method and application thereof.
[0006] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:
[0007] According to a first aspect of an embodiment of the present invention, the present invention provides a method for preparing a MOF-modified rice husk biochar composite material, the method comprising the following steps:
[0008] (1) placing dried rice husk powder in a high-temperature atmosphere furnace and heating it to obtain rice husk biochar;
[0009] (2) mixing rice husk biochar, FeCl3 and water to obtain a first solution, and mixing phthalic acid, NaOH and water to obtain a second solution;
[0010] (3) The first solution and the second solution are mixed, and the obtained mixture is heated, solid-liquid separated, washed, and dried to obtain the MOF-modified rice husk biochar composite material.
[0011] Furthermore, in step (1), the heating conditions are: heating to 300-700°C at a heating rate of 1-20°C / min and maintaining for 0.5-4h.
[0012] Further, in step (2), the mass ratio of rice husk biochar, FeCl3 and water is 1:10-30:500;
[0013] The mass ratio of phthalic acid, NaOH and water is 1-12:1:10-50.
[0014] Furthermore, in step (3), the mass ratio of the first solution to the second solution is 1-50:1;
[0015] The heating conditions are: placing in an electric heating blast drying oven at 60-150°C for 12-24h;
[0016] The washing conditions are: washing three times with deionized water and ethanol;
[0017] The drying conditions are: drying in a vacuum oven at 60-80° C. for 12 h.
[0018] According to a second aspect of an embodiment of the present invention, the present invention provides a MOF-modified rice husk biochar composite material, which is made by the method described in any one of the above items.
[0019] According to a third aspect of an embodiment of the present invention, the present invention provides the use of the MOF-modified rice husk biochar composite material as described above in rare earth ion recovery.
[0020] Furthermore, the rare earth ion is La 3+ .
[0021] According to a fourth aspect of an embodiment of the present invention, the present invention provides a method for recovering rare earth ions, the method comprising:
[0022] The MOF-modified rice husk biochar composite material as described above is mixed and shaken with a rare earth ion solution to separate the solid from the liquid.
[0023] Further, the mixing and oscillating conditions are: temperature of 10-40°C, time of 12-72h, and rotation speed of 150-250rpm;
[0024] The addition amount of the MOF-modified rice husk biochar composite material is 0.1-0.4 g / L;
[0025] The rare earth ion solution contains La 3+ The concentration range is 1-200 mg / L.
[0026] Biochar (BC) has extremely high practical value in removing environmental pollutants such as heavy metals and organic pollutants. At the same time, biochar is environmentally friendly, economical, and highly adaptable, and can transform a variety of agricultural and anthropogenic wastes such as rice husks, straw, and feces into wealth. The production of biochar also helps to mitigate the greenhouse effect. The adsorption effect of biochar mainly depends on its specific surface area and external functional groups. The modification strategy significantly increases the active sites of the original biochar, increases the specific surface area, and enhances the adsorption capacity.
[0027] Metal-organic framework (MOF) is a new type of crystalline porous material composed of metal nodes and organic ligands through coordination bonds. It has the advantages of large specific surface area and porosity, rich functional groups, etc. Compared with traditional adsorbents, it is very suitable for removing various pollutants in water. The biggest feature of MOF is the versatility and designability of its structure. The structure can be customized according to specific applications and selectively bind the required elements in the presence of different interferences.
[0028] The MOF of the present invention uses trivalent iron as the metal ion. Compared with divalent metals such as Zn and Cu, trivalent Fe can reach a higher valence state, thereby participating in stronger metal-ligand interactions and forming a MOF with higher hydrothermal stability. The chemical stability and hydrolytic stability of Fe-MOFs make them very suitable for adsorbing and removing pollutants from aqueous media. In addition, the presence of high-valent iron (III) and carboxylate residues will produce many active sites, thereby enabling the adsorption of pollutants. Although Lewis-acidic rare earth ions often form complexes with oxygen-containing functional groups and are easily adsorbed onto MOFs, the MOF powder has a small particle size and non-negligible water solubility, which limits its scope of application, especially in continuous flow systems. The MOF-modified biochar composite material not only retains the respective advantages of BC and MOF, such as porosity, high specific surface area and active sites, but also combines the large conjugated aromatic rings of BC with La 3+ The electrostatic attraction between the oxygen-containing functional groups of MOF and La 3+ The ligand exchange between them realizes the La 3+ This specific adsorption ability makes MOF-modified biochar composites very suitable for treating La-containing 3+ It has potential application value in wastewater or waste gas.
[0029] The embodiments of the present invention have the following advantages:
[0030] The present invention uses BC as a carrier to reduce the solubility of MOF, prevent secondary pollution, improve recyclability, and at the same time increase the pore volume of the composite material, increase active sites, and ultimately achieve efficient adsorption of rare earth ions by the composite material.
[0031] The MOF-modified rice husk biochar composite material provided by the present invention is a harmless and environmentally friendly material with the advantages of being non-toxic, having good chemical stability, etc., and at the same time, the preparation method is simple, the operability is strong, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0033] Figure 1 The optimized structure of the MOF-modified rice husk biochar composite material of Example 1 of the present invention calculated by DFT simulation and the La 3+ Adsorption model of
[0034] Figure 2 is a morphology diagram of the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0035] Figure 3 is an XRD diagram of the MOF-modified rice husk biochar composite material according to an embodiment of the present invention;
[0036] Figure 4 is a nitrogen adsorption-desorption isotherm diagram of the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0037] Figure 5 is a thermogravimetric analysis diagram of the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0038] Figure 6 is the FTIR graph of the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0039] Figure 7 is an XPS graph of the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0040] Figure 8 is the adsorption isotherm of rare earth ions by BC, MOF and MOF-modified rice husk biochar composite material of Example 1 of the present invention after 24 hours of oscillation;
[0041] Fig. 9is the adsorption kinetics of rare earth ions by the MOF-modified rice husk biochar composite material of Example 1 of the present invention;
[0042] Fig.10 is the selectivity of the MOF-modified rice husk biochar composite material of Example 1 of the present invention to rare earth ions;
[0043] Fig.11 The MOF-modified rice husk biochar composite material of Example 1 of the present invention is reusable. DETAILED DESCRIPTION
[0044] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a MOF-modified rice husk biochar composite material, and the preparation method thereof comprises the following steps:
[0047] (1) Under anaerobic conditions, 20 g of dried rice husk was placed in a high-temperature atmosphere furnace and heated to 400 °C at a heating rate of 10 °C / min and maintained at this temperature for 2 h to obtain rice husk biochar (denoted as BC).
[0048] (2) Dissolve 2.7 g FeCl3·6H2O in 50 mL water, add 0.1 g BC to the above solution, and ultrasonically treat it at room temperature for 1 h to obtain the first solution. Dissolve 1.66 g H2BDC and 0.32 g NaOH in 4 mL water in a beaker to obtain the second solution. Mix the above two solutions and ultrasonically treat them at room temperature for 1 h. Move the mixture to a reactor and place it in an electric heated blast drying oven at 100 ° C for 12 h. Separate the orange chemical by centrifugation and then wash it three times with deionized water and ethanol to remove residual organic linkers and solvents. The product was dried in a vacuum oven at 80 ° C overnight to obtain MOF-modified rice husk biochar composite material.
[0049] Example 2
[0050] This embodiment provides a MOF-modified rice husk biochar composite material, and the preparation method thereof comprises the following steps:
[0051] (1) Under anaerobic conditions, 20 g of dried rice husk was placed in a high-temperature atmosphere furnace and heated to 600 °C at a heating rate of 5 °C / min and maintained at this temperature for 1 h to obtain rice husk biochar (denoted as BC).
[0052] (2) Dissolve 1.35 g FeCl3·6H2O in 25 mL water. Add 0.05 g BC to the above solution and ultrasonically treat it at room temperature for 1 h to obtain the first solution. Dissolve 0.83 g H2BDC and 0.08 g NaOH in 4 mL water in a beaker to obtain the second solution. Mix the above two solutions and ultrasonically treat them at room temperature for 1 h. Move the mixture to a reactor and place it in an electric heated blast drying oven at 120°C for 24 h. Separate the orange chemical by centrifugation and then wash it three times with deionized water and ethanol to remove residual organic linkers and solvents. The product was dried in a vacuum oven at 60°C overnight (12 h) to obtain a MOF-modified rice husk biochar composite material.
[0053] Example 3
[0054] This embodiment provides a MOF-modified rice husk biochar composite material, and the preparation method thereof comprises the following steps:
[0055] (1) Under anaerobic conditions, 20 g of dried rice husk was placed in a high-temperature atmosphere furnace and heated to 500 °C at a heating rate of 15 °C / min and maintained at this temperature for 2.5 h to obtain rice husk biochar (BC).
[0056] (2) Dissolve 2.025 g FeCl3·6H2O in 50 mL water. Add 0.1 g BC to the above solution and ultrasonically treat it at room temperature for 1 h to obtain the first solution. Dissolve 0.62 g H2BDC and 0.24 g NaOH in 3 mL water in a beaker to obtain the second solution. Mix the above two solutions and ultrasonically treat them at room temperature for 1 h. Move the mixture to a reactor and place it in an electric heated blast drying oven at 110°C for 18 h. Separate the orange chemical by centrifugation and then wash it three times with deionized water and ethanol to remove residual organic linkers and solvents. The product was dried in a vacuum oven at 60°C overnight to obtain a MOF-modified rice husk biochar composite material.
[0057] Test Example 1
[0058] The performance of the MOF-modified rice husk biochar composite material of Example 1 was tested.
[0059] Density functional theory (DFT) is an important tool in computational chemistry for predicting material behavior. It provides insights into molecular adsorption, including adsorption structure, adsorption energy. DFT calculations are able to predict the theoretical structure of new adsorbents, which helps to understand the surface of the adsorbent and establish the ground state structure connected to the adsorbate. This knowledge can optimize molecular design and select appropriate adsorbents. DFT simulations can also calculate the adsorption mechanism of new adsorbents with rare earth ions, which enhances our understanding of rare earth recovery and helps to improve the design and effectiveness of adsorbents.
[0060] Figure 1 The optimized structure and La of the MOF-modified rice husk biochar composite material of Example 1 calculated by DFT simulation (the software modules are Devicestudio and BDF, respectively) 3+ Adsorption model. During the growth and preparation of MOF-modified rice husk biochar composites (denoted as BC@MIL-88b), organic ligands and metal ions in MOF were selectively bound to the smallest structural unit. As the MOF expanded, the smallest structural unit established ionic associations with the carbon framework around the oxygen functional groups of BC. The remaining ligands and metal ions combined near the attachment point to form the BC@MIL-88b secondary structural unit through self-assembly. During this process, some oxygen-containing functional groups of BC (including carboxyl, carbonyl and aldehyde groups) prevented the expansion of MOF. Combined with SEM analysis, it was found that the surface of BC was covered with rod-shaped MIL-88b structures. We used pure graphene structure to simulate the surface structure of aromatized biogenic BC to simplify the model calculation. Many studies have successfully used this strategy and achieved positive results. Considering the large cell structure of Fe-MOF, in order to improve the calculation efficiency, a cluster model with Fe as the node and a single ligand with carboxyl groups on the surface was selected. The optimal adsorption arrangement of BC@MIL-88b is shown in Figure 1 a. This structure has a significant negative adsorption energy, which indicates that the binding of La to these sites is spontaneous. The corresponding interactions are mainly composed of the formation of La-O bonds ( Figure 1 b) and La 3+ The π-π conjugation of the benzene ring causes ( Figure 1 c) From Figure 1 It can be seen that the La-O bond plays a significant role and the interaction is more stable. 3+ Adsorbed on BC@MIL-88b, the interaction energies are -10.52 and -10.51 kcal·mol -1 It can be seen that MOF has an important influence on the adsorption properties of BC surface.
[0061] Figure 2The scanning electron microscope (SEM) observation of the morphology of the MOF-modified rice husk biochar composite material of Example 1 shows that BC has an interconnected layered porous structure, a smooth surface, and no visible material attached, while MOF (denoted as MIL-88b, the preparation method of MIL-88b is: except for not adding BC, the rest of the content is consistent with steps (2) and (3) of Example 1) is composed of nanorods with a length and width of approximately 1 μm and 200 nm, respectively. BC@MIL-88b retains the layered porous structure of BC, but some MIL-88b particles block the pores, which may reduce the number of active sites. After testing, the pore volume of the MOF-modified rice husk biochar composite material of Example 1 is 0.147 cm 3 g -1 .
[0062] Figure 3 X-ray diffraction pattern (XRD) of the MOF-modified rice husk biochar composite material of Example 1 and diffraction peaks of BC, MIL-88b and standard MIL-88b samples.
[0063] As can be seen from the figure, the XRD pattern of BC@MIL-88b shows prominent sharp peaks, indicating its high crystallinity. The main peaks in the MIL-88b spectrum are consistent with the peaks in the corresponding crystal information file (2088535), which confirms the successful synthesis of this MOF. Similarly, the peaks of BC@MIL-88b are very similar to those of MIL-88b, but the diffraction angle is lower, which may be due to the diffusion of MOF to the BC surface or the formation of large gaps in the MOF crystals due to defects or impurities in the BC.
[0064] Figure 4 The nitrogen adsorption-desorption isotherm of the MOF-modified rice husk biochar composite material of Example 1. Theoretically, the decoration of BC surface by MOF should increase the specific surface area and pore volume of BC. However, the introduction of MOF particles may also hinder the internal voids, thereby reducing the specific surface area. The average pore size of BC@MIL-88b is 10.05nm, so it is mainly mesopores.
[0065] Figure 5 Thermogravimetric analysis of the MOF-modified rice husk biochar composite material of Example 1. The thermal stability of the composite adsorbent exceeds that of its constituent components. The thermogravimetric analysis of BC@MIL-88b has three weight loss stages. The first weight loss is between 30 and 110°C and is due to the evaporation of water physically adsorbed on the surface. The second weight loss (27.89%) occurs between 110 and 430°C, reflecting the evaporation of solvent molecules in the internal pores. The third weight loss (31.74-34.35%) occurs between 430-700°C due to ligand carbonization and MOF structure collapse.
[0066] Figure 6 FTIR images of the MOF-modified rice husk biochar composite material before and after adsorption of rare earth ions in Example 1. 3+ The solution was shaken at 250 rpm for 24 h at room temperature and then the solid and liquid were separated. The FTIR spectrum of BC@MIL-88b was at 3447.08 cm -1 There is an obvious OH peak at 1660.57 cm -1 (asymmetric stretch) and 1389.50cm -1 (Symmetric stretch) shows the carboxyl CO peak. 1500-1600cm -1 The peaks at 1253.74 and 1157.03 cm are attributed to the stretching vibration of the benzene ring skeleton, while the peaks at 1253.74 and 1157.03 cm -1 The peak at 552.01cm corresponds to the COC molecule. -1 The peak at 553.29 cm disappeared after adsorption and was replaced by -1 These data indicate that during the adsorption process, La 3+ Interaction with metal ions forms Fe-O-La covalent bonds. 3392.27cm -1 The peak at 2.300 nm weakened after adsorption, indicating that La 3+ It is adsorbed by hydroxyl substitution rather than direct binding to iron. 1500-1600cm -1 The change of the peak at indicates that the benzene ring structure is involved in the La 3+ Therefore, we conclude that during the adsorption process, the hydroxyl groups are replaced by La 3+ substituted, thus forming Fe-O-La bonds, which is consistent with the results of the adsorption kinetics experiment.
[0067] Figure 7 The XPS spectra of the MOF-modified rice husk biochar composite material before and after adsorption in Example 1. The adsorption conditions are as follows Figure 6 The Fe 2p spectrum shows characteristic Fe 2p at 728.58 and 724.78 eV. 1 / 2 The peaks at 716.78 and 711.78 eV show the characteristic Fe 2p 3 / 2Peaks. After adsorption, the above peaks red-shifted to 728.98, 725.28, 717.58 and 712.28 eV, indicating that electron transfer occurred in the Fe 2p valence band (possibly due to substitution of functional groups in the adsorbent). This change alters the chemical environment around Fe, indicating that an internal Fe-O-La complex may be formed). Fe-O (530.47 eV), -OH (531.87 eV) and OC=O (533.3 eV) peaks appeared in the O 1s spectrum. After adsorption, the -OH peak disappeared and was replaced by the peaks of Fe-O-La (531.98 eV) and La-O (532.48 eV). CC (284.8 eV), C-OH (285.92 eV), OC=O (287.11 eV) and carbonate (288.81 eV) peaks appeared in the C 1s spectrum. After adsorption, the C-OH and OC=O peaks shifted, and their area percentages decreased from 13% to 5% and 7% to 5%, respectively. Therefore, the reactive -OH group can be replaced by La, forming an internal Fe-O-La complex through ligand exchange and adsorbing La. 3+ These results are consistent with those of FTIR spectroscopy.
[0068] Figure 8 At the initial La 3+ Concentration is 5-100 mg L -1 Under the conditions of pH 6.0, La was obtained by stirring at 298 K and 250 rpm for 24 h. 3+ Adsorption isotherm. 3+ With the increase of concentration, BC@MIL-88b has a significant effect on La 3+ The adsorption capacity of La increases accordingly until it reaches equilibrium. 3+ The maximum adsorption capacity on BC@MIL-88b reached 288.89 mg g -1 .
[0069] Fig. 9 The effect of reaction time (3-600 min) on the La content of BC@MIL-88b was investigated under the conditions of temperature of 298 K and stirring rate of 250 rpm. 3+ (60mg L -1 ) The adsorption capacity increased with the passage of time, and the adsorption equilibrium was reached after 6 hours of reaction.
[0070] Fig.10 Tb 3+ , Y 3+ 、Lu 3+ 、Ce 3+ 、Al 3+ , Fe 3+ 、Na + , K+ , Ca 2+ Mg 2+ As interfering cations, at 60 mg L -1 La 3+ The concentration and interference concentration were 10, 20 and 40 mg L -1 Under the conditions of BC@MIL-88b, the effect of La 3+ The selectivity of Ce 3+ 、Al 3+ , Fe 3+ 、Na + , K + , Ca 2+ Mg 2+ To La 3+ There was no obvious interference with the adsorption of Tb 3+ , Y 3+ He Lu 3+ To La 3+ The higher the concentration, the stronger the interference. 3+ , Y 3+ He Lu 3+ The concentration is much lower than this concentration.
[0071] Fig.11 The recyclability of BC@MIL-88b was tested at 298 K using 0.05 M HCl as the eluent. After four cycles, BC@MIL-88b had a good recyclability for 5 mg L -1 La 3+ The adsorption rate of the solution was maintained above 93%, and the desorption rate exceeded 80% in all cycles before the last cycle.
[0072] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing a MOF-modified rice husk biochar composite material, characterized in that: The method comprises the following steps: (1) placing dried rice husk powder in a high-temperature atmosphere furnace and heating it to obtain rice husk biochar; (2) mixing rice husk biochar, FeCl3 and water to obtain a first solution, and mixing phthalic acid, NaOH and water to obtain a second solution; (3) The first solution and the second solution are mixed, and the obtained mixture is heated, solid-liquid separated, washed, and dried to obtain the MOF-modified rice husk biochar composite material.
2. The method for preparing the MOF-modified rice husk biochar composite material according to claim 1, characterized in that: In step (1), The heating conditions are: heating to 300-700° C. at a heating rate of 1-20° C. / min and maintaining for 0.5-4 h.
3. The method for preparing the MOF-modified rice husk biochar composite material according to claim 1, characterized in that: In step (2), The mass ratio of rice husk biochar, FeCl3 and water is 1:10-30:500; The mass ratio of phthalic acid, NaOH and water is 1-12:1:10-50.
4. The method for preparing the MOF-modified rice husk biochar composite material according to claim 1, characterized in that: In step (3), The mass ratio of the first solution to the second solution is 1-50:1; The heating conditions are: placing in an electric heating blast drying oven at 60-150°C for 12-24h; The washing conditions are: washing three times with deionized water and ethanol; The drying conditions are: drying in a vacuum oven at 60-80° C. for 12 h.
5. A MOF-modified rice husk biochar composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 4.
6. Use of the MOF-modified rice husk biochar composite material according to claim 5 in rare earth ion recovery.
7. The use according to claim 6, characterized in that: The rare earth ion is La 3+ .
8. A method for recovering rare earth ions, characterized in that: The method comprises: The MOF-modified rice husk biochar composite material according to claim 5 is mixed and shaken with a rare earth ion solution to separate the solid from the liquid.
9. The method according to claim 8, characterized in that The mixing and oscillating conditions are: temperature of 10-40°C, time of 12-72h, and rotation speed of 150-250rpm; The addition amount of the MOF-modified rice husk biochar composite material is 0.1-0.4 g / L; The rare earth ion solution contains La 3+ The concentration range is 1-200 mg / L.
Citation Information
Patent Citations
Preparation method and application of bimetallic organic framework material Fe / Mg-MIL-88B
CN109232901A
Magnetically invasive plant hydrothermal carbon-Fe-based MIL-100 adsorbent as well as preparation method and application thereof
CN117482898A
Iron modified charcoal gel composite material and preparation method and application thereof
CN118059814A
Preparation method and application of Fe-MOF biochar composite adsorption material
CN118059826A
Preparation of MOF-COF hybrid organic framework material and application of MOF-COF hybrid organic framework material in rare earth separation
CN118240236A